Wilhelm II: Into the Abyss of War and Exile, 1900–1941. (March 2016) - Fitzpatrick, Matthew P
Abstract : Wilhelm II: Into the Abyss of War and Exile, 1900–1941. By John C.G. Röhl (Cambridge: Cambridge University Press, 2014), pp.1562, AU$97.95 (cloth).